Resource nationalism: the intersection of politics and economics - Deyi Xu; Shiquan Dou; Yongguang Zhu; Jinhua Cheng (Humanities & Social Sciences Communications)
Abstract Resource nationalism has a complex economic, political, and cultural history and reality. The evolution of the supply and demand structure of the global mineral metal market influences it. It is closely linked to the “economic-political” system within resource-rich countries. We analyze the ‘economic-political’ logic of resource nationalist behavior using the two-tier game theory. We examine 261 cases of resource nationalism since 1990 and test the theoretical hypotheses using quantitative techniques. The results show that rising mineral prices are the main trigger for contemporary resource nationalism. However, ideology, institutional quality, social climate, and economic dependence within resource countries play a non-negligible role. Resource wealth dependence in host countries makes it difficult for policymakers to escape national resource interventions. We argue that (1) The global economic trading system imbalance is the root of resource nationalism. (2) Resource nationalism is an endeavor by resource-rich countries to seek entitlements from mineral resource endowments. (3) Resource nationalism is not a zero-sum competition in the national economic trading system. In the face of the potential risks posed by resource nationalism to the global supply of minerals, the relevant interest groups should have sufficient strategic reserves to cope with the possible game of interests.